A140 IBD DASHBOARD: AN INNOVATIVE E-HEALTH PROGRAM FOR PROVIDING EQUAL ACCESS TO QUALITY CARE FOR ALL INFLAMMATORY BOWEL DISEASE PATIENTS. (1st March 2018) - Sutton, R T; Wishart, E; Dhami, N; Sadowski, D; Siffledeen, J; Sauve, M; Hundal, R; Ismond, K; van Zanten, S; Huang, V
Abstract: Background: Individuals with inflammatory bowel diseases (IBD) often live remote to specialized tertiary care centers. In traditional practices, this impedes the close surveillance of symptoms, objective markers of disease (C-reactive protein (CRP), fecal calprotectin (FCP), and optimization of therapies recommended to achieve the best health outcomes. Emerging self-management and e-Health strategies have improved medication adherence and reduced duration and severity of disease flares. Our center developed an innovative eHealth platform, the "IBD Dashboard", a secure, online portal where patients can upload their self-collected data at regular intervals to provide a cross-sectional and longitudinal assessment of disease state. The IBD clinician can modify therapy accordingly in near real-time to prevent disease relapse. Aims: To test the feasibility and impact of the IBD Dashboard for providing optimized care in a virtual environment to IBD patients based upon patient self-reported data. Methods: Physicians across Alberta invited their adult IBD patients to enroll into the study. Patients were instructed to submit clinical scores every month on the IBD dashboard, and complete a home FCP (Buhlmann IBDoc FCP test) at baseline, 3 and 6 months. Those who had elevated FCP repeated FCP 1 and 2 months later. Feasibility questions included ease of use, impact on management decisions of the physician, patient medication adherence, and patient acceptance. Results: A total of 29 patients have consented to the study thus far, including 12 (41.4%) females and 14 (48.3%) with Crohn's disease. The median age is 37.0 years (IQR: 32.0 to 50.0). Medication snapshot: 9 (31.0%) on 5-ASA, 2 (6.9%) on steroids, 6 (20.7%) on immunomodulators, 19 (65.5%) on biologics, and 4 (13.8%) taking no medications. A total of 21 (65.5%) have completed baseline FCP. The median FCP was 276.0 mcg/g (IQR: 64.0 to 956.0), with 11 (52.4%) having an FCP ≥250 mcg/g. Of these patients with elevated FCP, 5 (45.5%) self-report symptoms consistent with disease remission (<5 modified Harvey Bradshaw or <2 partial Mayo). Conclusions: Our feasibility pilot study on the use of IBD dashboard, an innovative eHealth platform, is showing near seamless integration in the routine clinical management of remote patients. It is accessible and easy to use for both physicians and patients. The high proportion of patients with elevated FCP, half of which were asymptomatic, suggests a need for close surveillance irrespective of clinical disease symptoms. Funding Agencies: Alberta Health Services Digestive Health Strategic Clinical Network (DC SCN)